High-throughput dissection of AAV-host interactions: the fast and the curious - Herrmann, Anne-Kathrin; Grimm, Dirk (Journal of molecular biology, 2018)
Over 50 years after its initial description, adeno-associated virus (AAV) remains the most exciting but also most elusive study object in basic or applied virology. On the one hand, its simple structure not only facilitates investigations into virus biology but, combined with the availability of numerous natural AAV variants with distinct infection efficiency and specificity, also makes AAV a preferred substrate for engineering of gene delivery vectors. On the other hand, it is striking to witness a recent flurry of reports that highlight and partially close persistent gaps in our understanding of AAV virus and vector biology. This is all the more perplexing considering that recombinant AAVs have already been used in >160 clinical trials and recently been commercialized as gene therapeutics. Here, we discuss a reason for these advances in AAV research, namely, the advent and application of powerful high-throughput technology for dissection of AAV-host interactions and optimization of AAV gene therapy vectors. As relevant examples, we focus on the discovery of (i) a “new” cellular AAV receptor, AAVR, (ii) host restriction factors for AAV entry, and (iii) AAV capsid determinants that mediate trafficking through the blood-brain barrier. While items i/ii are prototypes of extra- or intracellular AAV host factors that were identified via high-throughput screenings, item iii exemplifies the power of molecular evolution to investigate the virus itself. In the future, we anticipate that these and other key technologies will continue to accelerate the dissection of AAV biology and will yield a wealth of new designer viruses for clinical use